2019
DOI: 10.1155/2019/6932572
|View full text |Cite
|
Sign up to set email alerts
|

How Accurately Can Prostate Gland Imaging Measure the Prostate Gland Volume? Results of a Systematic Review

Abstract: Aim. The measurement of the volume of the prostate gland can have an influence on many clinical decisions. Various imaging methods have been used to measure it. Our aim was to conduct the first systematic review of their accuracy. Methods. The literature describing the accuracy of imaging methods for measuring the prostate gland volume was systematically reviewed. Articles were included if they compared volume measurements obtained by medical imaging with a reference volume measurement obtained after removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
6
43
0
Order By: Relevance
“…Additionally, it shows good reproducibility and is used several studies to evaluate prostatic volume, as was recently shown in a published meta-analysis. (12) The median prostatic weight based on surgical specimens obtained in our study was 42g, which is in correspondence with that found in other studies, such as by Mayer et al, which demonstrated a median weight of 47.6g, and Badani et al, of 49.9g. (13,14) It is possible that, in our study, this value was a little lower due to the fact that sample had many patients under 60 years of age (n=24; 28%), which could justify a lower prostatic weight due to smaller lower volume in the transition zone.…”
Section: ❚ Resultssupporting
confidence: 92%
“…Additionally, it shows good reproducibility and is used several studies to evaluate prostatic volume, as was recently shown in a published meta-analysis. (12) The median prostatic weight based on surgical specimens obtained in our study was 42g, which is in correspondence with that found in other studies, such as by Mayer et al, which demonstrated a median weight of 47.6g, and Badani et al, of 49.9g. (13,14) It is possible that, in our study, this value was a little lower due to the fact that sample had many patients under 60 years of age (n=24; 28%), which could justify a lower prostatic weight due to smaller lower volume in the transition zone.…”
Section: ❚ Resultssupporting
confidence: 92%
“…However, TRUS of the prostate is a routine, low cost procedure in urology clinics which can reliably assess prostate volume. 16 Therefore, accurate PSAd estimates can be obtained before mpMRI without altering the clinical workflow. Applying decision thresholds of 0.078 ng/ml 2 for PSAd and 0.082 for the threshold probability of the multivariate model would have resulted in a net reduction of 25% and 29% of prostate mpMRI scans, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is unlike TRUS, which is considered a routine prebiopsy procedure which can reliably estimate prostate volume. 16 A recent review article concluded that sufficiently accurate prostate volume measurements were obtained by the 2 imaging modalities with MRI being only slightly more accurate. 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both DRE and PSA measurement have some utility in estimating prostate volume but they are not accurate enough . Conversely, TRUS measurement of prostate volume has been shown to correlate well with radical prostatectomy specimens . This is important because a larger volume prostate has been linked with increased blood loss .…”
mentioning
confidence: 99%